Strength of Intentional Effort Enhances the Sense of Agency - Minohara, Rin; Wen, Wen; Hamasaki, Shunsuke; Maeda, Takaki; Kato, Motoichiro; Yamakawa, Hiroshi; Yamashita, Atsushi; Asama, Hajime (Frontiers in Psychology, 2016)
Sense of agency refers to the feeling of controlling one’s own actions, and the experience of controlling external events with one’s actions. The present study examined the effect of strength of intentional effort on sense of agency. We manipulated the strength of intentional effort using three types of buttons that differed in the amount of force required to depress them. We used a self-attribution task as an explicit measure of sense of agency. The results indicate that strength of intentional effort enhanced self-attribution when action-effect congruency was unreliable. We concluded that intentional effort importantly affects the integration of multiple cues affecting explicit judgments of agency when the causal relationship action and effect was unreliable.